Framing Media Tentang Influencer Sebagai Jaringan Informasi Pemerintah : Analisis Media Republika.co.id, Detik.com dan Kompas.com Periode Agustus 2020 - Shelma Salsabila; Frida Kusumastuti (Universitas Terbuka, 2021)
News framing about influencers, it is known how the mass media fight for their interests. The study analyzed three news stories about government influencers from three different media during the period of August 2020. The study used a qualitative approach with the Pan & Kosicki framing analysis method. The results show that Republika.co.id's framing emphasizes on finding data that causes debate. While Detik.com's framing directs the existence of influencers as corruption events, and Kompas.com's framing provides an overview of influencers who have a strong position as an information network because they are key opinion leaders in the digital era.